Body sway in biathlon shooting - Bozsik, A.; Bretz, K.; Kaske, R. J. (ISBS - Conference Proceedings Archive (Konstanz), 1995)
The characteristics and performances of biathlon shooting can't be compared with other shooting sports without taking into consideration the loading of cross-country racing. Significant correlation ( ~k.6265; n=13) has been found between the results of Romberg test with closed eyes and the co-ordination test containing tasks of moving the centre of mass of the body on a pre-determined path and surface reflected by a computer monitor. We assume that the former is mostly, the later is partially influenced by the proprioception system. In our tests, the barrel was parallel to the X axis of the imaginary co-ordinate system in which the force platform is placed. The X components of the body sway (mediolateral direction) were significantly less during the period of shooting than the Y components (anteroposterior direction). The dominant frequencies were generally higher to the mediolateral direction. The equilibrium factor of performance in this kind of sport can be investigated using the present methods, but further investigations are necessary to make the generalisation of results possible. Stochastic moving of centre of mass of the body occur while shooting. On the displacement diagram the signal to noise ratio is determined by the level of signals correlating with the shot and the spontaneous body sway amplitudes as mentioned above